The Influence of Price and Promotion on Purchase Decisions: Case Study from Cimory Yogurt Products - Ivantan, I. (Manunggal Halim Jaya, 2025)
This study examines the influence of price and promotion on consumer purchasing decisions of Cimory yogurt products distributed through Miss Cimory Indonesia. The research employs a quantitative approach with a survey method, involving data collection through questionnaires. The study population consists of all consumers who purchased Cimory products through Miss Cimory agents in the Pondok Hijau Ciputat area during 2023, totaling 1,830 individuals. Using the Slovin formula with a 10% margin of error, the study determined a sample size of 95 respondents selected through random sampling. Data analysis was conducted using multiple linear regression. The results of the analysis revealed that both price and promotion have a significant effect on purchasing decisions. This finding suggests that effective pricing and promotional strategies positively influence consumer decision-making. Therefore, companies are encouraged to optimize these variables to enhance purchase intention and strengthen customer loyalty. The research contributes to the marketing field by highlighting the importance of key elements in the marketing mix that directly influence consumer behavior.